Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/hjh.0000000000002973
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure and hypertension control in children with autosomal recessive polycystic kidney disease: clinical experience from two central European tertiary centres

Abstract: Objective : Arterial hypertension is a common complication in patients with autosomal recessive polycystic kidney disease (ARPKD), occurring in 33-75% of children when measured by office blood pressure (OBP). Ambulatory blood pressure monitoring (ABPM) is a superior tool for investigating blood pressure relative to OBP. The aim of our study was to investigate the prevalence and control of hypertension in children with ARPKD based on ABPM.Methods: This retrospective study evaluated 36 children with ARPKD and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The median age at the first ABPM was 4.4 years and the average interval between the first and the last recording was 5 years. Confirming previous reports (Dell et al, 2016), the initial evaluation showed hypertension in 94% of patients, of which only one-third were well controlled with antihypertensive therapy (Seeman et al, 2022). At the last evaluation, the prevalence of hypertension remained stable (86%), but two-third of patients were now adequately treated.…”
Section: Pathogenesis and Prevalence Of Hypertensionsupporting
confidence: 86%
See 2 more Smart Citations
“…The median age at the first ABPM was 4.4 years and the average interval between the first and the last recording was 5 years. Confirming previous reports (Dell et al, 2016), the initial evaluation showed hypertension in 94% of patients, of which only one-third were well controlled with antihypertensive therapy (Seeman et al, 2022). At the last evaluation, the prevalence of hypertension remained stable (86%), but two-third of patients were now adequately treated.…”
Section: Pathogenesis and Prevalence Of Hypertensionsupporting
confidence: 86%
“…The estimated prevalence of hypertension in published studies ranges from 33% to 75% (Deget et al, 1995;Zerres et al, 1996;Guay-Woodford and Desmond, 2003;Bergmann et al, 2005;Dell, 2011;Guay-Woodford et al, 2014). Hypertension develops even in the first weeks of life and is often difficult to control, requiring early combined therapy with different antihypertensive drugs (Deget et al, 1995;Zerres et al, 1996;Guay-Woodford et al, 2014;Chinali et al, 2019;Seeman et al, 2022). Hypertension is not always associated with kidney failure.…”
Section: Pathogenesis and Prevalence Of Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the autosomal recessive form of polycystic kidney disease (ARPKD), MH has been found in a most recent study in only 5% of patients, apparently because of the high prevalence of sustained hypertension evident also by office BP measurements (94%) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The demographic and clinical data, antihypertensive medication, symptoms, and complications of children with ARPKD are shown in Table 1. Thirteen patients were described in our earlier paper on ambulatory blood pressure in ARPKD [11].…”
Section: Methodsmentioning
confidence: 99%